Anatomical characterization of Cre driver mice for neural circuit mapping and manipulation - Harris, Julie A.; Hirokawa, Karla E.; Sorensen, Staci A.; Gu, Hong; Mills, Maya; Ng, Lydia L.; Bohn, Phillip; Mortrud, Marty; Ouellette, Benjamin; Kidney, Jolene; Smith, Kimberly A.; Dang, Chinh; et al. (Frontiers in Neural Circuits, 2014)
Significant advances in circuit-level analyses of the brain require tools that allow for labeling, modulation of gene expression, and monitoring and manipulation of cellular activity in specific cell types and/or anatomical regions. Large-scale projects and individual laboratories have produced hundreds of gene-specific promoter-driven Cre mouse lines invaluable for enabling genetic access to subpopulations of cells in the brain. However, the potential utility of each line may not be fully realized without systematic whole brain characterization of transgene expression patterns. We established a high-throughput in situ hybridization, imaging and data processing pipeline to describe whole brain gene expression patterns in Cre driver mice. Currently, anatomical data from over 100 Cre driver lines are publicly available via the Allen Institute’s Transgenic Characterization database, which can be used to assist researchers in choosing the appropriate Cre drivers for functional, molecular, or connectional studies of different regions and/or cell types in the brain.